124k views
23 votes
(r^-7)^6 im looking for anwser

User Simplelenz
by
5.4k points

1 Answer

6 votes

Answer:

( r^-7 )^6 = r^-42 ( in exponential form )

( or )

1 / r^42 ( in fractional form )

Explanation:

( r^-7 )^6

Formula : -

( a^m )^n = a^( mn )

Here,

a = r

m = - 7

r = 6

mn

= - 7 * 6

= - 42

Hence,

( r^-7 )^6 = r^-42 ( in exponential form )

( or )

( r^-7 )^6 = 1 / r^42 ( in fractional form )

User Sad Comrade
by
4.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.